Free Flap Reconstruction for Burn Injuries: A Single-Center Retrospective Comparison of Primary and Secondary Cases - Daihun Kang; Hyungwoo Wang; Seung Eun Hong; Youn Hwan Kim (Journal of Clinical Medicine, 2026)
Background: Most acute burn wounds are managed with skin grafting, yet many patients later develop contractures requiring secondary free flap reconstruction, which is widely believed to be more demanding than reconstruction in the acute setting. This clinical impression has rarely been quantified. This study compared the characteristics, operative parameters, and outcomes of primary and secondary free flap reconstruction for burn injuries. Methods: In this single-center retrospective study, 65 consecutive free flap reconstructions performed in 55 patients between 2012 and 2025 were categorized as primary (acute wound coverage during the initial burn admission, n = 35) or secondary (reconstruction of established scar contracture after discharge from acute care, n = 30). Demographics, burn extent, injury-to-reconstruction interval, prior operations, flap selection, operative time, secondary procedures, and complications were compared. Multivariable linear regression with sequential adjustment for age, sex, defect location, defect size, total body surface area (TBSA) burned, and flap complexity was used to estimate the adjusted difference in operative time. Results: Secondary patients were younger (40.8 vs. 55.1 years), more often female (70% vs. 29%), had larger burns (median TBSA 18% vs. 3%) and larger defects (348.5 vs. 203.3 cm2), and underwent reconstruction a median of 534 days after injury versus 30 days in the primary group. Operative time was longer in secondary cases (236.3 vs. 170.7 min; p < 0.001), and this association persisted after adjustment for age, sex, defect location, defect size, TBSA, and flap complexity (adjusted difference, 55.2 min; 95% CI, 20.4–90.1; p = 0.002) and in sensitivity analyses accounting for repeated procedures in the same patient. Flap complexity distribution and the frequency of secondary procedures did not differ between groups. Thoracodorsal vessel-based flaps were used in 90.8% of cases, and overall flap survival was 98.5%. Conclusions: Secondary free flap reconstruction for burn scar contracture required approximately 55 min longer than primary reconstruction of acute burn wounds, independently of defect size, burn extent, and flap complexity, whereas flap survival and the need for subsequent procedures were similar. Whether earlier free flap coverage of wounds at high risk of contracture could reduce this burden warrants prospective evaluation.